Nagative and positive Values in Pashto Tapa - Sajid, Muhammad; Gul, Sana; Khan, Rizwan Ullah (sourcecoder, 2023)
"Tapa" is fundamental in Pashto genres. Thematically, this genre has a lot to offer. Apart from other topics, negative and positive values are also mentioned in this genre. Negative values refer to those elements which lead man and human life towards failure and positive values are those which lead man and life towards success. This research paper examines the negative and positive values in Pashto "Tapa".